Rancang Bangun Aplikasi E-Commerce Kerajinan Bambu Berbasis Android untuk Desa Belega - Muhammad Abel Jollando; Putu Wira Buana; Fajar Purnama (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2024)
The development of information and communication technology in Indonesia has growing up significantly in the last few years. Thus, there are many opportunities to digitize the business processes of a business and business ecosystem. One of them is in the field of digital economy by adapting business processes into a digital platform, as well as designing an E-Commerce platform in a village that has commodities inside it and increase the product visibility. This research uses Belega Village as a case study location considering that this village has commodities in the form of bamboo crafts. Research was conducted to build an android-based bamboo craft E-Commerce application which is expected to increase product visibility. The application itself is built using the Agile Development method using a Sprint model. This application is built with a microservices architecture with Express.js technology as a backend service and React Native to create client applications and PostgreSQL as a DBMS. The results of this research are in the form of an android-based E-Commerce application that is expected to increase the visibility of products from bamboo crafts from Belega Village.